TNF-α and TGF-β Contributes in Recurrent Otorrhea of Active Mucosal Chronic Otitis Media - Dewi Pratiwi; Marisa Rizqiana; Adisetya Wicaksono; Defitaria Permatasari; Ratna Dwi Restuti; Tri Nugraha Susilawati; Sutarno Sutarno (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Active mucosal chronic otitis media (COM) is prevalent in lower-income countries and is associated with recurrent episodes of otorrhea due to chronic inflammation of the middle ear. Cytokines, which are well-known for their effects on the immune system, play an important role in the inflammatory response and tissue remodeling. The specific contributions of proinflammatory and immunoregulatory cytokines in the pathophysiology of active mucosal COM remain unclear. This study aimed to compare the levels of serum tumor necrosis factor (TNF)-α and transforming growth factor (TGF)-β in patients with active mucosal COM vs. healthy subjects.METHODS: Total 20 subjects with active mucosal COM and 20 healthy subjects participated in this study. The levels of serum TNF-α and TGF-β were measured using enzyme-linked immunosorbent assay (ELISA).RESULTS: The average level of serum TNF-α in subjects with active mucosal COM was significantly higher compare to the healthy subjects (46.373±41.76 pg/mL vs. 15.021±7.16 pg/mL; p=0.004). In contrast, the average level of serum TGF-β in subjects with active mucosal COM was lower compared to the healthy subjects, although the difference is not statistically significant (9.963±3.2 ng/mL vs. 11.78±8.48 ng/mL; p=0.552). Further analysis showed that in subjects with active mucosal COM, the levels of serum TNF-α had a medium positive correlation with the level of TGF-β (r=0.525; p=0.018).CONCLUSION: TNF-α and TGF-β, which are proinflammatory and immunoregulatory cytokines, may contribute to the pathogenesis of recurrent episodes of otorrhea in an active mucosal COM.KEYWORDS: tumor necrosis factor-α, transforming growth factor-β, active mucosal chronic otitis media